Operative outcomes of thoracoscopic lobectomy for non-small-cell lung cancer. (October 2015) - Tane, Shinya; Nishio, Wataru; Okuma, Hiromichi; Ogawa, Hiroyuki; Hokka, Daisuke; Tane, Kenta; Tanaka, Yugo; Uchino, Kazuya; Yoshimura, Masahiro; Maniwa, Yoshimasa
Aim: We examined the advantages of thoracoscopy over thoracotomy in terms of perioperative outcomes and toleration of adjuvant chemotherapy. Methods: Between April 2010 and March 2013, 657 patients with non-small-cell lung cancer who underwent lobectomy were classified into thoracoscopy (308 patients) and thoracotomy (349 patients) groups and compared. Results: The thoracoscopy group had less blood loss compared to the thoracotomy group ( p < 0.001). When limiting the analysis to pathological stage I patients, the results were similar ( p < 0.001). In addition, the difference in blood loss between the 2 groups was greater in patients with severe pleural adhesions. The postoperative morbidity of the thoracoscopy group was significantly less than that of the thoracotomy group (13.3% vs. 21.2%, p < 0.001), and this result was similar when analyzing the pathological stage I patients (12.6% vs. 20.6%, p = 0.001). A higher percentage of the thoracoscopy group received both the full planned course and dose of adjuvant chemotherapy compared to the thoracotomy group (84.2% vs. 65.8%, p = 0.032). Conclusions: These results indicate that totally thoracoscopic lobectomy is the more beneficial surgical approach with regard to the incidence of postoperative complications and toleration of adjuvant chemotherapy.